Low serum uric acid levels in patients with acute central nervous system viral infections. Issue 18 (13th December 2017) - Li, Xiang; Tong, Qiaowen; Xie, Dewei; Chen, Zhibo; Pan, Sipei; Zhang, Xu; Dong, Wanli
Abstract : Most acute central nervous system (CNS) viral infections lead to either encephalitis or meningitis. Many neurotropic viruses may cause CNS dysfunctions through various mechanisms including oxidative stress. Serum uric acid (SUA) levels, which are associated with oxidative stress and antioxidant status, are reduced in patients with various neurological disorders, including multiple sclerosis. We investigated the possible correlation between SUA levels and clinical disease status in patients with acute CNS viral infections. We measured SUA concentrations in 336 individuals, including 179 healthy individuals and 157 patients with acute CNS viral infections. We found that the patients had lower SUA levels than the healthy individuals did irrespective of sex. Effective therapy significantly increased SUA levels. The patients' SUA levels were correlated inversely with outcomes as measured with the Glasgow Outcome Scale. SUA levels may be a biomarker for predicting treatment outcomes and prognoses for patients with acute CNS viral infections with inflammatory components.